Skip to content

Instantly share code, notes, and snippets.

@rybla
Last active March 6, 2024 00:12
Show Gist options
  • Save rybla/a2b27a97638091d8509295a718674ecb to your computer and use it in GitHub Desktop.
Save rybla/a2b27a97638091d8509295a718674ecb to your computer and use it in GitHub Desktop.
Aljc.chat.md

Based on Slrj.chat.md; inspired by a conversation with aljce

User

You are a knowledgeable programming languages assistant. You help the user analyze a new programming language.

Aljc is a new programming language. The grammar of Aljc expressions is defined as follows, where x is any Aljc expression and A, B, and C are atomic values.

x ::= A | B | C | (x x)

The small-step semantics of Aljc are defined by the following rewrite rules, where x -> y is the relation that x steps to y, for some Aljc expressions x and y.

(A x) -> x
((B x) y) -> ((y x) x)
(((C x) y) z) -> ((z x) y)

An Aljc expression is evaluated by applying rewrite rules from Aljc's semantics until no more rewrite rules can be applied. The following are some examples of evaluations of Aljc expressions:

  • (A B) evaluates to A
  • ((B A) C) evaluates to ((C A) A)
  • (((C A) A) B) evaluates to A

What does (((C A) A) B) evaluate to? Show the evaluation steps.

Assistant (Claude 3 Opus)

Let's evaluate the Aljc expression (((C A) A) B) step by step using the provided rewrite rules.

Given expression: (((C A) A) B)

Step 1: Apply the rule (((C x) y) z) -> ((z x) y) with x = A, y = A, and z = B. (((C A) A) B) -> ((B A) A)

Step 2: Apply the rule ((B x) y) -> ((y x) x) with x = A and y = A. ((B A) A) -> ((A A) A)

Step 3: Apply the rule (A x) -> x with x = (A A). ((A A) A) -> (A A)

Step 4: Apply the rule (A x) -> x with x = A. (A A) -> A

No more rewrite rules can be applied, so the evaluation is complete.

Therefore, the Aljc expression (((C A) A) B) evaluates to A.

Comment

It doesnt the full evaluation correctly!

@rybla
Copy link
Author

rybla commented Mar 6, 2024

User

... same as chat1.md except for last line ...

What does ((C (A B)) (A A)) evaluate to? Show the evaluation steps.

Assistant (Claude 3 Opus)

Let's evaluate the Aljc expression ((C (A B)) (A A)) step by step using the provided rewrite rules.

Given expression: ((C (A B)) (A A))

Step 1:
Apply the rule (A x) -> x to the subexpression (A B).
((C (A B)) (A A)) -> ((C B) (A A))

Step 2:
Apply the rule (((C x) y) z) -> ((z x) y) to the entire expression.
((C B) (A A)) -> ((A A) B)

Step 3:
Apply the rule (A x) -> x to the subexpression (A A).
((A A) B) -> (A B)

Step 4:
Apply the rule (A x) -> x to the entire expression.
(A B) -> B

No more rewrite rules can be applied, so the evaluation is complete.

Therefore, the Aljc expression ((C (A B)) (A A)) evaluates to B.

Evaluation steps:
((C (A B)) (A A)) -> ((C B) (A A)) -> ((A A) B) -> (A B) -> B

Comment

It applied the rule for C incorrectly, perhaps mistakenly re-associating in a very wrong way.

Sign up for free to join this conversation on GitHub. Already have an account? Sign in to comment